Study protocol for key interventions to improve the follow-up adherence postcervical precancerous lesion treatment in Ethiopia: a pragmatic randomised controlled trial - Adamu Addissie; Eva Johanna Kantelhardt; Eric Sven Kroeber; Sefonias Getachew; Muluken Gizaw; Abel Shita; Alemnew Destaw; Eyerusalem Getachew; Miresa Midaksa; Sophie Rossner (BMJ Open)
Introduction The follow-up adherence after treatment for a positive screening test is critical for preventing the development of screen‐detected abnormalities in cervical cancer. Yet, this poses a major challenge in developing countries like Ethiopia, emphasising the urgency for intervention strategies. Our trial aims to assess which strategies would be effective in improving adherence to follow-up after suspicious cervical lesion treatment in Ethiopia. Thus, the objective of this study is to evaluate key interventions to improve the follow-up adherence rate among women treated for suspicious cervical lesions in primary healthcare settings in Ethiopia.Method and analysis We will employ a pragmatic randomised control trial study design, using Consolidated Standards of Reporting Trials guidelines for reporting and a Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) checklist for developing the protocol, to evaluate intervention effectiveness. These interventions are: (a) structured nurses-led telephone call reminders, (b) home-visit reminders led by health extension workers and (c) application-based automated short message service text reminders. The standard care involves only receiving oral follow-up advice and a baseline follow-up card. The planned start date is 1 November 2024, with an anticipated end date of 1 November 2025. Our study will include women aged 30–49 who are HIV-negative and those over 25 who are HIV-positive, and who have been treated for suspicious cervical lesions after a positive visual inspection with acetic acid (VIA) screening, as per Ethiopian Ministry of Health guidelines for cervical cancer screening eligibility. The required sample size is 460, with 115 participants per arm. Study participants in the intervention group will receive the stated interventions plus the standard care, while the control group will receive only the standard care. The interventions will be delivered three times annually: 4 months from baseline, then at 8 months and finally at 12 months before the appointment due date. The primary outcome of our study is the proportion of adherence to follow-up recommendations, which will be measured by rescreening (VIA) after 1 year (11–13 months after the first screening). Descriptive statistics, χ2 test (Fisher’s exact test), binary logistic regression analysis and intention-to-treat will be used to describe and interpret the results.Ethics and dissemination The trial protocol has been approved by the institutional review board of Addis Ababa University with protocol number (008/24/SPH). Trial results will be disseminated to study participants, national and international audiences through workshops, conferences and publications in reputable journals.Trial registration number NCT06515301.